The Ameliorative Effect of Coumarin on Copper Toxicity in Citrus sinensis: Insights from Growth, Nutrient Uptake, Oxidative Damage, and Photosynthetic Performance - Wei-Lin Huang; Hui Yang; Xu-Feng Chen; Fei Lu; Rong-Rong Xie; Lin-Tong Yang; Xin Ye; Zeng-Rong Huang; Li-Song Chen (Plants)
Excessive copper (Cu) has become a common physiological disorder restricting the sustainable production of citrus. Coumarin (COU) is a hydroxycinnamic acid that can protect plants from heavy metal toxicity. No data to date are available on the ameliorative effect of COU on plant Cu toxicity. ‘Xuegan’ (Citrus sinensis (L.) Osbeck) seedlings were treated for 24 weeks with nutrient solution containing two Cu levels (0.5 (Cu0.5) and 400 (Cu400) μM CuCl2) × four COU levels (0 (COU0), 10 (COU10), 50 (COU50), and 100 (COU100) μM COU). There were eight treatments in total. COU supply alleviated Cu400-induced increase in Cu absorption and oxidative injury in roots and leaves, decrease in growth, nutrient uptake, and leaf pigment concentrations and CO2 assimilation (ACO2), and photo-inhibitory impairment to the whole photosynthetic electron transport chain (PETC) in leaves, as revealed by chlorophyll a fluorescence (OJIP) transient. Further analysis suggested that the COU-mediated improvement of nutrient status (decreased competition of Cu2+ with Mg2+ and Fe2+, increased uptake of nutrients, and elevated ability to maintain nutrient balance) and mitigation of oxidative damage (decreased formation of reactive oxygen species and efficient detoxification system in leaves and roots) might lower the damage of Cu400 to roots and leaves (chloroplast ultrastructure and PETC), thereby improving the leaf pigment levels, ACO2, and growth of Cu400-treated seedlings.